Analysis of Prothrombin Time (PT) and Activated Partial Thromboplastin Time (aPTT) in Patients with Acute Myocardial Infarction on Anticoagulation Therapy to Assess the Thrombogenic Potential (Medico Legal Update, 2021)
Background: Activated partial thromboplastin time and prothrombin time measures the action of theintrinsic and extrinsic pathways of coagulation needed to maintain homeostasis in the body. We studiedaPTT and PT levels in acute myocardial infarction (AMI) patients on anticoagulation therapies and normalsubjects. The aim of the study is to assess aPTT and PT in patients of acute MI on anticoagulation.Materials And Method: This study was conducted on 42 patients with chest pain and 84 AMI patients,admitted to Dhiraj hospital, Vadodara. The AMI patients were classified into STEMI (n=28) and NSTEMI(n=56). PT and aPTT were assayed on a fully automatic Stago-coagulometer instrument (STA CompactMax).Conclusion: Patients with STEMI had mean aPTT of 40.79 ± 1.83 s, NSTEMI had 41.33 ± 2.06 s, aPTT incontrol subjects was 31.35 ± 0.48 s. Patients with acute coronary syndrome had significantly higher levelsof aPTT. Patients with STEMI has PT of 17.42 ± 5 s, NSTEMI had 18.56 ± 5 s. Patients on anticoagulationtherapy had higher aPTT and PT values.Both PT and aPTT are high in acute MI patients on anticoagulants.The elevations in PT values were more than 3 fold greater than aPTT suggesting that PT has a highersensitivity for predicting blood clotting capacity in patients already on anticoagulations.